2017
DOI: 10.1111/1745-9125.12139
|View full text |Cite
|
Sign up to set email alerts
|

Age and Its Relation to Crime in Taiwan and the United States: Invariant, or Does Cultural Context Matter?*

Abstract: Current empirical and theoretical understanding of the relation between age and crime is based almost entirely on data from the United States and a few prototypical Western societies for which age‐specific crime information across offense types is available. By using Western databases, Hirschi and Gottfredson (1983) projected that the age distribution of crime is always and everywhere robustly right‐skewed (i.e., sharp adolescent peak)—a thesis that is both contested and widely accepted in criminology and soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 73 publications
1
30
0
1
Order By: Relevance
“…Similarly, in the United States youth between 15 and 29 years correspond to 20.9% of the total population, but are responsible for 49.8% of all arrests for violent crimes (S1 Fig). While there is growing evidence for differences in the specific age distribution of crime across countries [12,13], the overall shape of this distribution is consistent and studies regularly find that violent behavior declines as individuals age into later adulthood. Since violent crime tends to be most common amongst youth, countries with younger populations–all else equal–should have higher homicide rates [14].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the United States youth between 15 and 29 years correspond to 20.9% of the total population, but are responsible for 49.8% of all arrests for violent crimes (S1 Fig). While there is growing evidence for differences in the specific age distribution of crime across countries [12,13], the overall shape of this distribution is consistent and studies regularly find that violent behavior declines as individuals age into later adulthood. Since violent crime tends to be most common amongst youth, countries with younger populations–all else equal–should have higher homicide rates [14].…”
Section: Introductionmentioning
confidence: 99%
“…A series of recent research studies conducted by Steffensmeier and colleagues (Steffensmeier, Lu, and Kumar 2019;Steffensmeier, Lu and Na 2020;Steffensmeier, Zhong, and Lu 2017) examined whether Hirschi and Gottfredson's (1983) thesis on the age-crime curve, which is considered a major theory of developmental and life-course criminology and desistance (see Weaver 2019), applies to Asian countries, including Taiwan (Steffensmeier et al 2017), India (Steffensmeier et al 2019), and South Korea (Steffensmeier et al 2020). They have found that Hirschi and Gottfredson's (1983) thesis does not directly apply to these Asian countries because the age-crime patterns in these countries, particularly the peak age of crime, are distinct from those in the US, where the thesis was developed (Steffensmeier et al 2017(Steffensmeier et al , 2019(Steffensmeier et al , 2020. Suzuki et al (2018) systematically reviewed existing studies that examined the extent to which five main criminological theories, including strain, social learning, control, routine activity, and developmental and life-course, are supported in the Asian context.…”
Section: Towards Culture-inclusive Criminology In Asiamentioning
confidence: 99%
“…Additionally, the tendency to commit crimes can change over time, regardless of age (Piquero, Farrington, & Blumstein, ). Recent comparative studies that used crime data from Taiwan and the USA found a considerable divergence from the age effect on crime (Steffensmeier, Zhong, & Lu, ). We therefore include population age diversity as a variable to investigate its relationship with crime, but with a prediction that different measures of diversity will identify different relationships.…”
Section: Literature Review and Explanatory Variablesmentioning
confidence: 99%